2020
DOI: 10.1074/jbc.ra119.011400
|View full text |Cite
|
Sign up to set email alerts
|

PYHIN1 regulates pro-inflammatory cytokine induction rather than innate immune DNA sensing in airway epithelial cells

Abstract: Animal cells use pattern-recognition receptors (PRRs) to detect specific pathogens. Pathogen detection mounts an appropriate immune response, including interferon and cytokine induction. The intracellular PRR-signaling pathways that detect DNA viruses have been characterized, particularly in myeloid cells. In these pathways, cGMP-AMP synthase (cGAS) and the pyrin and HIN domain family member (PYHIN) protein interferon-γ–inducible protein 16 (IFI16) detect DNA and signal via stimulator of interferon genes prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…The human ALR Pyrin-only protein 3 does not contain a HIN200 domain and is reported to act as an inflammasome inhibitor ( Khare et al., 2014 ). Human PYHIN1 was reported to act as an IFN-I-inducing DNA sensor (see Box 4 , cytosolic DNA and Type-I IFN) but has also recently been shown to control TNF and IL-6 release downstream of STING activation ( Massa et al., 2020 ). Better understanding of the mammalian ALRs is not only important to our own antiviral defense but also that of livestock and important mammalian viral reservoirs, such as bats for paramyxovirues and coronaviruses ( Drexler et al., 2012 ; Li et al., 2005 ).…”
Section: Main Textmentioning
confidence: 99%
“…The human ALR Pyrin-only protein 3 does not contain a HIN200 domain and is reported to act as an inflammasome inhibitor ( Khare et al., 2014 ). Human PYHIN1 was reported to act as an IFN-I-inducing DNA sensor (see Box 4 , cytosolic DNA and Type-I IFN) but has also recently been shown to control TNF and IL-6 release downstream of STING activation ( Massa et al., 2020 ). Better understanding of the mammalian ALRs is not only important to our own antiviral defense but also that of livestock and important mammalian viral reservoirs, such as bats for paramyxovirues and coronaviruses ( Drexler et al., 2012 ; Li et al., 2005 ).…”
Section: Main Textmentioning
confidence: 99%
“…Even the DNA viruses, like human papillomavirus (HPV), Epstein-Barr Virus (EBV), Kaposi's sarcoma-associated herpesvirus (KSHV), and Merkel cell polyomavirus induce TLR9 detected type I interferon (IFN) secretion [159]. These viruses also activate several PRR families like RLRs, cGAS-STING, and PYHIN protein culminating in the NF-κB pathway like SARS CoV [160,161]. Additionally, several bacteria Figure 2.…”
Section: Does Sars-cov-2 Infections In Immunosuppressive Conditions Wmentioning
confidence: 99%
“…2A). To validate the findings, a dual-luciferase reporter assay was performed using A549 cells, as this is the most used cell line in previous stduies investigating lung cancer (27,28). The results demonstrated that the miR-140-5p mimic significantly reduced the luciferase activity of A549 cells compared with NC mimic, whereas miR-140-5p inhibitor significantly increased luciferase activity compared with the NC inhibitor group.…”
Section: Oip5-as1 Promotes Nsclc Metastasismentioning
confidence: 85%